Analisis Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Struktur Modal Terhadap Nilai Perusahaan - Danisya Zalza Billa Putri Supriyanto; Zaky Machmuddah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the relationship between firm value (Tobin's Q) and profitability (ROA), liquidity (CR), company size (SIZE), and capital structure (DER). Using a purposive selection technique, we examined a sample of 60 industrial enterprises that were listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Using IBM SPSS 26, we performed a multiple linear regression analysis, which showed that each of these characteristics had a significant impact on the value of the company.